Implementasi Pengawasan Otoritas Bandar Udara Wilayah IV Terhadap Flight Approval Penerbangan Niaga Berjadwal Bandar Udara Internasional I Gusti Ngurah Rai - Italiano Duta Achdyat Iskak; Awan (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
Abstract; Nowadays, air transportation has a very vital role, as one of the most important modes of transportation today. Completeness of documents, to prepare safeguards to create aviation safety and security is now very important, even though it seems trivial, this is very important to prepare security and safety for air transportation. It was reported by news.detik.com written by Edward Febriyati in 2016, that Airfast airline faked a flight permit for an MD – 82 aircraft carrying 101 passengers from Cengkareng to Denpasar, Ujung pandang and Timika. Moving on from this problem, the aim of this research is to find out how the supervision of the Region IV Airport Authority is implemented in cases of counterfeiting flight permits for scheduled commercial flights. This research focuses on the Region IV Airport Authority which carries out the task of supervising scheduled commercial flights starting from 7 August to 11 August 2023. The research method used in this research is qualitative. The reason why this research uses qualitative research methods is because the sources used are primary and secondary data sources. Primary data was obtained through interview and observation techniques taken from 3 informants and all of these informants were inspectors from the Region IV Airport Authority, while secondary data was taken from documentation data and equipped with literacy related to the research title. Government supervision of the granting of flying permits by the Directorate General of Civil Aviation is in practice represented by the Airport Authority. In the form of law enforcement related to aviation regulations, the government stipulates Law Number 1 of 2009 concerning Aviation. The results obtained are that the role of the airport authority is very important for the safety and security of national aviation in this region of Indonesia. The airport authority is responsible for granting this permit and if it is dangerous for the company or passengers, sanctions are regulated in Law Number 1 of 2009 concerning aviation. In their supervision, air business entities should be able to comply with and implement the laws and regulations that have been issued by the Directorate of Civil Aviation, which ultimately creates safe and comfortable transportation. Keywords: Air Transportation, Flying Permit Supervision, Airport Authority.